Febrile Convulsion Knowledge Scale for Parents/Caregivers: A Validity and Reliability Study - TOKSÖZ, FATMA; Açıkgöz, Ayfer; Mutlu, Fezan Şahin; Sayık, Dilek (W.B. Saunders, 2023)
Background The primary worry of parents/caregivers in relation to fever is the potential for their child to experience a seizure as a result. The literature suggests that parents/caregivers need to be informed about febrile convulsion. Thus, this study sought to develop the ‘Febrile Convulsion Knowledge Scale for Parents/Caregivers’. Design and methods It is a methodological study comprising 984 parents/caregivers who were accessible online between 07/04/2021 and 30/06/2022. After creating the scale item pool's construction, expert opinions were sought to evaluate the scale, and a content validity analysis was conducted. Subsequent analysis included exploratory and confirmatory factor analyses, Cronbach's Alpha, and a test-retest reliability assessment of the scale data. Results The scale was found to consist of 8 items and 3 factors according to the factor analyses. Exploratory factor analysis indicated that the scale explained 72.783% of the variance. The scale's reliability analysis produced a Cronbach's Alpha score of 0.679, indicating good internal consistency, and it was consistent with test-retest measures (t = −0.660, p = 0.514). Conclusions It has been determined that the scale is a valid and reliable scale for evaluating the knowledge of parents/caregivers regarding febrile convulsions. Practice implications It is advisable for pediatric nurses to routinely use the devised scale with families of children who are vulnerable to febrile convulsion and impart instruction based on the findings derived from the scale.
Keywords: Caregiver; Development; Febrile Convulsion; Parent; Scale